Epizootiology of Rabies in Fergana Region and Measures for its Preventio - Saydaliyev, D. I.; Shapulatova, Z. J.; Sobirov, S. F. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article provides information about the epizootology of rabies and the relationship of the disease with wild fauna, which is a reservoir of infection. It also discusses the general and specific measures taken to prevent the spread of the disease in the Fergana region. In order to assess its effectiveness, an analysis was made of the degree of vaccination of animals in the region over the past 7 years, reflecting the dependence of the prevalence of rabies among animals on specific prophylaxis during 2015-2021.